Four decades of research on landslides: comparative analysis of the Central America Geological Journal - Peraldo Huertas, Giovanni (2024)
The article aims to investigate how many papers on landslides have been published in the Central American Geological Journal (RGAC), as well as the distribution of these between men and women. The result shows that 3 % of the total articles published over the forty years of the journal focus on the topic of landslides. Regarding author signatures, 75 % correspond to men and 25 % to women. In terms of authorship, 60 % of the articles were written by men, while 40 % have mixed authorship (men and women). No articles written exclusively by women have been recorded. These results were compared with findings from other journals, such as the Central American Geographical Journal, the Geographical Journal of the Pan American Institute of Geography and History (IPGH), the Chilean Geological Journal, the Journal of the Argentine Geological Association, and the Internacional Geophysics Journal, yielding similar trends. However, there is a lack of deeper research to explain these results, leaving the possibility for future inquiries open to better understand the reasons behind these data.